Sanggar Anak Desa Sebagai Pelopor Pelestarian Dan Pemberdayaan Warisan Lokal Untuk Mewujudkan Budaya Berbasis Pendidikan Di Desa Konda Satu Kabupaten Konawe Selatan - Chairan Zibar L. Parisu; Windi Putri Handina (Prodi PGSD Unsultra, 2026)
The Organizational Capacity Strengthening Program (PPK Ormawa) of the HMPS PGSD, Southeast Sulawesi University, was carried out in Konda Satu Village as a response to the declining interest of the younger generation in Tolaki culture, which has increasingly been eroded by modernization. This program aims to establish the Sanggar Anak Desa as a center for cultural preservation, enhance teacher capacity through a Tolaki culture–based teaching module, and actively involve the community and traditional institutions in education-based artistic activities. The implementation methods included planning, execution, and evaluation stages. The results of the program indicate a growing interest among children in traditional dance, improved teacher competence in integrating culture into learning, and the establishment of an institutionalized art studio formalized through a Village Head Decree (SK). In addition, the Tolaki Mini Dance Festival served as the peak cultural appreciation event, encouraging active community participation. Overall, this program contributes to strengthening cultural identity, building a culture-based educational ecosystem, and promoting the sustainability of Tolaki cultural preservation in Konda Satu Village.